The use of Twitter in professional meetings of information professional sector: case study - Traver Vallés, Paula; Cobarsí Morales, Josep (Revista General de Información y Documentación, 2012)
Microblogging’s rise in last years poses questions about his use and potential in several contexts. This work, specifically, plans to analyze an example of Twitter’s use as communication tool in professional meeting in information sector. So, a case study about X Workshop Rebiun is done. Empyrical work combines participative observation, data logs, interviews and content analysis. We found evidence about Twitter’s plurality uses and Twitter’s capacity to enhance a virtual community emerged from this event.